Investigating Effects of Coal Flotation Waste on Aged Hot Mix Asphalt Performance - Abbastabardelavar, Mohammadreza; Izadi, Amir; Asadiamiri, Fereshte (Civil Engineering Journal, 2018)
The present study was an attempt to investigate the effect of fresh and old coal flotation waste (coal waste), used as asphalt filler and additive, on the properties of hot asphalt mixtures in aged and un-aged condition. In this experimental study, fresh and old coal flotation waste, obtained from the Central Alborz Coal Washing Plant, were used to produce filler specimens (100% Wt.) as substitutes for limestone powder and asphalt additive (7% w.t). Finally, the performance of the asphalt mixture containing flotation waste was evaluated using Marshall Stability and indirect tensile tests. The afore-mentioned compounds were used to produce specimens under short-term aging conditions and the results were compared with other results obtained under un-aged condition. The results indicate that flotation waste improved performance of hot mix asphalt under short-term aging conditions.